Strengthening critical thinking in the mathematics classroom: a pandemic experience. - Jiménez , Yasmin; Vesga, Grace (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The objective of this research was to strengthen the critical thinking of high school students, through the analysis of social situations of their interest, so that the use of mathematical concepts would help them to understand them, take a position and provide solutions. Eighteen eleventh grade students from a private educational institution in the municipality of Madrid, Colombia, participated and analyzed the situation generated by covid-19, specifically vaccination and its effect on the family environment. An action research methodological design was used. It was possible to demonstrate that, by involving in the mathematics classroom problems with which the students feel identified, critical thinking is strengthened, since the participants became autonomously interested in a problem situation, deepened their understanding and reacted by providing solutions.